Beneficial role of the probiotic mixture Ultrabiotique on maintaining the integrity of intestinal mucosal barrier in DSS-induced experimental colitis. (June 2013) - Toumi, Ryma; Abdelouhab, Katia; Rafa, Hayet; Soufli, Imene; Raissi-Kerboua, Djamila; Djeraba, Zineb; Touil-Boukoffa, Chafia
Abstract The etiology of inflammatory bowel diseases which include ulcerative colitis (UC) and Crohn disease has not yet been clarified. Several hypotheses suggest a change in composition of gut microflora along with an impaired mucosal barrier that lead to excessive mucosal immunologic responses. Increased production of nitric oxide (NO) contributes greatly to the tissue injury caused by chronic inflammation. Evidence indicates that the mucus layer covering the epithelium is altered during UC and experimental colitis. Our aim in this study was to investigate the potential therapeutic effect of probiotic during DSS-induced colitis by modulating the immune system and colonic mucus production. For that purpose, the probiotic formulation Ultrabiotique® (Lactobacillus acidophilus, Bifidobacterium lactis, Lactobacillus plantarum and Bifidobacterium breve) was administered daily for 7 d to mice with colitis. Probiotic supplementation improved clinical symptoms and histological alterations observed during DSS induced colitis. Ultrabiotique® treatment down regulated the NO production by peritoneal macrophages of DSS-treated mice and enhanced mucus production in both DSS-treated and healthy mice. In conclusion, the modification of microflora by the Ultrabiotique® played a beneficial role in maintaining the integrity of the intestinal mucosal barrier and promoted tissue repair.